2011
DOI: 10.1007/s11075-011-9494-1
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive algorithm for the Thomas–Fermi equation

Abstract: A free boundary value problem is introduced to approximate the original Thomas-Fermi equation. The unknown truncated free boundary is determined iteratively. We transform the free boundary value problem to a nonlinear boundary value problem defined on [0,1]. We present an adaptive algorithm to solve the problem by means of the moving mesh finite element method. Comparison of our numerical results with those obtained by other approaches shows high accuracy of our method.Keywords Thomas-Fermi equation · Adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…The approximations of y ′ (0) computed by the present method and their relative errors are shown in Table 1. Obviously, this method is convergent by increasing the number of collocation points and obtaining suitable L. The comparison of the initial slope y ′ (0) calculated by the present work with values obtained by Liao [31], Khan [32], Yao [41] and Zhu et al [35] is given in Table 2, which shows that the present solution is highly accurate. Table 3 shows the approximations of y(x) obtained by the method proposed in this paper for N = 7 and L = 0.0958885, and those obtained by Khan [32] and Liao [42].…”
Section: Numerical Solution Of the Thomas-fermi Equationsupporting
confidence: 53%
See 2 more Smart Citations
“…The approximations of y ′ (0) computed by the present method and their relative errors are shown in Table 1. Obviously, this method is convergent by increasing the number of collocation points and obtaining suitable L. The comparison of the initial slope y ′ (0) calculated by the present work with values obtained by Liao [31], Khan [32], Yao [41] and Zhu et al [35] is given in Table 2, which shows that the present solution is highly accurate. Table 3 shows the approximations of y(x) obtained by the method proposed in this paper for N = 7 and L = 0.0958885, and those obtained by Khan [32] and Liao [42].…”
Section: Numerical Solution Of the Thomas-fermi Equationsupporting
confidence: 53%
“…(12) and (15) on Eq. (22) we define Kobayashi result [40] y ′ (0) = −1.588071 Table 2 Comparison between methods in [31,32,41,35] and the present method for y ′ (0). As in a typical tau method and using Eq.…”
Section: Numerical Solution Of the Thomas-fermi Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of methods: Zaitsev et al [40] showed that the Adams-Bashforth and Runge-Kutta methods to solve this equation on unbounded domains are ill-conditioned, hence, researchers have used the methods of numerical and semi-analytical for solving the equation, and some researchers can calculate very good solutions. For example, authors of [55,57,58,59,60,61,64,68,70] used the analytical methods for solving the equation and Amore et al [68] were able to calculate the best solution using Pade-Hankel method, correct to 26 decimal places. Authors of [54,56,62,63,65,66,67] used the numerical methods for solving the equation and Parand & Delkhosh [73] were able to calculate the best solution using the combination of the quasilinearization method and the fractional order of rational Chebyshev collocation method, correct to 37 decimal places.…”
Section: Resultsmentioning
confidence: 99%
“…The original problem has been formulated as a new free boundary value problem. Additionally, an adaptive algorithm for the Thomas-Fermi equation by means of the moving mesh finite element method has been developed [31].…”
Section: Introductionmentioning
confidence: 99%